A marginalização das mulheres gordas nas relações de trabalho em emissoras de televisão de João Pessoa/PB - Souza, Jayane Evellen de Fatima Cruz de (2024)
This dissertation has the general objective of understanding how fat women's work relationships occur within open television stations in João Pessoa/PB, TV Manaíra, an affiliate of Rede TV in Paraíba; TV Correio, a Record TV affiliate in Paraíba; TV Cabo Branco, a TV Globo affiliate in Paraíba. The authors and main themes of this study are “work relations” from the perspective of Jaime Campos (1971), “woman in the job market” with the author Laís Abramo (2007), “fat woman’s body” in Maria’s conceptions Luísa Jimenez (2021) and Nathália Rangel (2018), “organizational practices” with Theodore Shatscky (2005), in addition to Baldin and Munhoz (2011) with the “snowball theory”. It is clear that the fat woman's body is stigmatized and socially marginalized, which causes this to leak into organizations. However, it is not something that necessarily happens in a planned manner on the part of society towards managers, organizational rules and subjects. This scenario can also be seen from the opposite perspective, in which women are unable or unwilling to see themselves as fat, and therefore, express marginalization within television stations in Perso. This is possible to see through self-identification and the feeling of non-acceptance of one's own body.